Shotgun metagenomic sequencing reveals the influence of artisanal dairy environments on the microbiomes, quality, and safety of Idiazabal, a raw ewe milk PDO cheese - Gorka Santamarina-García; Min Yap; Fiona Crispie; Gustavo Amores; Cathy Lordan; Mailo Virto; Paul D. Cotter (Microbiome)
Abstract Background Numerous studies have highlighted the impact of bacterial communities on the quality and safety of raw ewe milk-derived cheeses. Despite reported differences in the microbiota among cheese types and even producers, to the best of our knowledge, no study has comprehensively assessed all potential microbial sources and their contributions to any raw ewe milk-derived cheese, which could suppose great potential for benefits from research in this area. Here, using the Protected Designation of Origin Idiazabal cheese as an example, the impact of the environment and practices of artisanal dairies (including herd feed, teat skin, dairy surfaces, and ingredients) on the microbiomes of the associated raw milk, whey, and derived cheeses was examined through shotgun metagenomic sequencing. Results The results revealed diverse microbial ecosystems across sample types, comprising more than 1300 bacterial genera and 3400 species. SourceTracker analysis revealed commercial feed and teat skin as major contributors to the raw milk microbiota (45.6% and 33.5%, respectively), being a source of, for example, Lactococcus and Pantoea, along with rennet contributing to the composition of whey and cheese (17.4% and 41.0%, respectively), including taxa such as Streptococcus, Pseudomonas_E or Lactobacillus_H. Functional analysis linked microbial niches to cheese quality- and safety-related metabolic pathways, with brine and food contact surfaces being most relevant, related to genera like Brevibacterium, Methylobacterium, or Halomonas. With respect to the virulome (virulence-associated gene profile), in addition to whey and cheese, commercial feed and grass were the main reservoirs (related to, e.g., Brevibacillus_B or CAG-196). Similarly, grass, teat skin, or rennet were the main contributors of antimicrobial resistance genes (e.g., Bact-11 or Bacteriodes_B). In terms of cheese aroma and texture, apart from the microbiome of the cheese itself, brine, grass, and food contact surfaces were key reservoirs for hydrolase-encoding genes, originating from, for example, Lactococcus, Lactobacillus, Listeria or Chromohalobacter. Furthermore, over 300 metagenomic assembled genomes (MAGs) were generated, including 60 high-quality MAGs, yielding 28 novel putative species from several genera, e.g., Citricoccus, Corynebacterium, or Dietzia. Conclusion This study emphasizes the role of the artisanal dairy environments in determining cheese microbiota and, consequently, quality and safety. Video Abstract